Yet another careful re-examination of the SAD hypothesis. Issue 3 (27th May 2014) - S. Khaled, Mohammed; P. Keef, Stephen
Abstract : Purpose: – The focus is on the seasonal affective disorder SAD hypothesis of Kamstra, Kramer and Levi (KKL). Examines the arguments advanced by KKL (2012) in their reply to the criticisms of the hypothesis raised by Kelly and Meschke (2010). Design/methodology/approach: – Uses a mixture of research synthesis and standard statistical analysis to investigate the reliability of the claims raised and the veracity of the statistical arguments. Findings: – The synthesis of the literature, and of the empirical models employed therein, raises questions about the validity of the SAD hypothesis. Originality/value: – Offers a rigorous analysis of whether there is a sound statistical basis for the SAD hypothesis which is frequently cited in the literature as support for the importance of behavioural finance.